Archaeological record of earthquake ruptures in Tell Ateret, the Dead Sea Fault. Issue 10 (9th October 2015) - Ellenblum, Ronnie; Marco, Shmuel; Kool, Robert; Davidovitch, Uri; Porat, Roi; Agnon, Amotz
Abstract: The archaeological Tell Ateret (North Israel), constructed on the active Dead Sea Fault, was intermittently settled for over six millennia. Structures on the Tell that have been offset by earthquake ruptures provide a remarkable record of alternating construction and slip. We excavated the site in order to resolve the geometry and to time the earthquake rupture history back to the earliest settlement. The measurements of faulted archaeological walls are complemented with data from historical documents, numismatic analysis, and geological observations. We report three newly discovered offsets that add to two previously resolved slip events (the 20 May 1202 and 30 October 1759 earthquakes), completing a three millennia archaeoseismic record. The oldest offset measuring at least ~2 m bisected Iron Age IIA fortifications. The second offset, the largest of all five, reaching ~2.5 m, is dated to circa 142 BCE The third, whose post‐Hellenistic date is not determined, is of ~1.5 m, possibly resulting from multiple earthquakes. We constrain the time of the largest offset by a hoard of 45 coins, the latest of which had been minted 143/142 BCE. Indicative pottery and historic texts support the year 143/142 as terminus post‐quem of the rupture at this site. These observations, together with a new kinematic approach, show uneven slip distribution in time and variable amounts of slip along the Jordan Gorge segment of the Dead Sea Fault. We suggest, based on previous palaeomagnetic measurements, that distributed deformation west of Tell Ateret can explain the apparent missing slip of 4.5 ± 3.5 m since the Hellenistic times. Key Points: Structures offset by earthquake ruptures provide a three millennia record of slip We add three newly discovered offsets to two previously resolved events The ruptures exhibit uneven slip distribution in time and variable slip amounts